PRINCIPIUL GRAŢIERII: POSIBILITATEA DE REÎNTOARCERE LA ESENŢĂ - USM ADMIN (Moldova State University, 2009)
A personality is not an absolute worth because a persona's notion includes a contradiction, (COHN Widersinn) double nature in causative / temporal limited in time and space, but can aspire to become and absolute worth by its unity of design to come back to essence (Cf.2.L.B.). Meaning of grace is a right axiological principle which is general in human engagement consists in proposing to au individual a possible opportunity of realization in space of Universe, by respect of the following exigencies: possibility of obtaining; capacity of continued formation capacity of auto- regulation, possibility of creative recon fining of itself, capacity of increasing with help of spirituality, possibility of a personality's recon fining of exactly social overall value. In the presented contexture insist above the first permanence of human engagement. Possibility of returning to essence: - Understanding a truth in identity of becoming; - Promotion of good buy what is it: practice of virtue as overall decisive integrity; - ,,Happiness consists in knowing of yourself"/ Aristotle [1]; - Reason and revelation - permanent background of human identity; - Free arbitrator - criteria of responsibility filings of yourself.